Recommendations for the detection and diagnosis of Niemann-Pick disease type C: An update. Issue 6 (December 2017) - Patterson, Marc C.; Clayton, Peter; Gissen, Paul; Anheim, Mathieu; Bauer, Peter; Bonnot, Olivier; Dardis, Andrea; Dionisi-Vici, Carlo; Klünemann, Hans-Hermann; Latour, Philippe; Lourenço, Charles M.; Ory, Daniel S.; et al.
Abstract: Purpose of review: Niemann-Pick disease type C (NP-C) is a neurovisceral disorder that may be more prevalent than earlier estimates. Diagnosis of NP-C is often delayed; a key aim for clinical practice is to reduce this delay. Recently, substantial progress has been made in the field of NP-C screening and diagnosis, justifying an update to the existing recommendations for clinical practice. Recent findings: New biomarker profiling and genetic analysis technologies are included as first-line diagnostic tests for NP-C. Most diagnoses can now be confirmed by combination of biomarker and genetic analyses. Filipin staining may facilitate diagnosis in uncertain cases. Recommendations are provided for psychiatrists, neuro-ophthalmologists, and radiologists, and on screening within specific at-risk patient cohorts. The NP-C diagnostic algorithm has been updated and simplified. Summary: This publication provides expert recommendations for clinicians who may see patients presenting with the signs and symptoms of NP-C, including general practitioners, pediatricians, neurologists, and psychiatrists.